To Know Our Many Selves: From the Study of Canada to Canadian Studies - Dirk Hoerder (Athabasca University Press, 2010)
To Know Our Many Selves profiles the history of Canadian Studies, which began as early as the 1840s with the Study of Canada. Professor Dirk Hoerder discusses this comprehensive examination of culture by highlighting its unique interdisciplinary approach, which included both sociological and political angles. Years later, as the study of other ethnicities was added to the cultural story of Canada, a solid foundation was formed for the nation's master narrative. Against this background, To Know Our Many Selves focuses on why Canadian Studies may be used as a sound model for the study of other societies in a frame of Transcultural Societal Studies.